2019
DOI: 10.3168/jds.2018-15477
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an individual cow concentrate strategy on production and behavior

Abstract: The aim of this study was to investigate the effects of a concentrate strategy based on the individual cow partial mixed ration (PMR) intake compared with a flat rate. Half of the cows were fed the individual concentrate strategy, whereas the other half were fed the control strategy. The individually fed cows were offered a concentrate proportion equal to 30% of the ad libitum intake of the PMR in the automatic milking system, and the control cows were offered 3 kg of concentrate/d in the automatic milking sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 33 publications
1
20
1
Order By: Relevance
“…Similarly, Vasseur et al (2012) report a complex interaction between parity, stage of lactation, and type of housing. The only longitudinal study reported to date found that lying times in both Holstein and Jersey cows were lower in first-parity cows during the first months of lactation, and then this difference between parities disappeared (Henriksen et al, 2019;Munksgaard et al, 2020). We found no evidence to help us decide whether these age-related changes reflect changes in the animal's welfare.…”
Section: Age and Paritycontrasting
confidence: 63%
See 2 more Smart Citations
“…Similarly, Vasseur et al (2012) report a complex interaction between parity, stage of lactation, and type of housing. The only longitudinal study reported to date found that lying times in both Holstein and Jersey cows were lower in first-parity cows during the first months of lactation, and then this difference between parities disappeared (Henriksen et al, 2019;Munksgaard et al, 2020). We found no evidence to help us decide whether these age-related changes reflect changes in the animal's welfare.…”
Section: Age and Paritycontrasting
confidence: 63%
“…Thus, we will focus on milking and feeding in our review of time constraints. Friend et al (1977) reported sizable negative correlations (ranging from −0.61 to −0.85) between the daily durations of feeding and lying down for cows in freestall systems, but small increases in feeding time (<1 h/d) do not result in changes in lying time (Henriksen et al, 2019). As expected, larger increases in feeding time lead to a reduced time spent lying down.…”
Section: Time Constraints Due To Feeding and Milkingmentioning
confidence: 65%
See 1 more Smart Citation
“…In both experiments, a control treatment was compared with experimental treatments with different types of adjustments in concentrate allowance in the robot (Henriksen, 2019). Treatment was included in the statistical analysis of the current study to adjust for variation due to treatment; however, a description of the exact treatments and effects of the treatments is provided by Henriksen (2019). Hence, for the current study, the cows were studied as a single cohort allocated to various treatments.…”
Section: Methodsmentioning
confidence: 99%
“…ICS can be applied in many ways, and a variety of interpretations can be made regarding the variable or variables to which ICS is related. In some studies it is applied according to MY, BW and estimated food intake (Cassel et al ., 1982; Maltz et al ., 1991, 1992 a , 1992 b ; Spahr et al ., 1993; Bossen and Weisbjerg, 2009; Bossen et al ., 2009) or as a percentage of the basic measured mixture consumed (Henriksen et al ., 2018). Neither stage of lactation nor reproduction status have been included in these ICS decision-making processes.…”
Section: Nutritionmentioning
confidence: 99%